2020
DOI: 10.1186/s13041-020-00578-5
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the time and/or mode of delivery differentially modulates early development in mice

Abstract: Delivery is a complex biological process involving hormonal and mechanical stimuli that together condition the survival and development of the fetus out of the womb. Accordingly, changes in the time or way of being born are associated with an alteration of fundamental biological functions and hypothesized to promote the emergence of neurodevelopmental disorders. Hence, the steadily rise in preterm birth and cesarean section (CS) delivery rates over the past years has become a worldwide health concern. In our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
(76 reference statements)
0
4
2
Order By: Relevance
“…Previous work in mice has found that CS pups either produce more calls on PND-9 [45][46][47] or produce an equivalent number of calls to VD counterparts [40,48] or USVs with decreased amplitudes [40], however, these studies were all in mice at a later stage of development than the current work. Our prior study of VD vole pups on PNDs 1 and 4 found that exposure to prenatal OXT led to increased USV production [34].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Previous work in mice has found that CS pups either produce more calls on PND-9 [45][46][47] or produce an equivalent number of calls to VD counterparts [40,48] or USVs with decreased amplitudes [40], however, these studies were all in mice at a later stage of development than the current work. Our prior study of VD vole pups on PNDs 1 and 4 found that exposure to prenatal OXT led to increased USV production [34].…”
Section: Discussioncontrasting
confidence: 77%
“…Previous work in mice has found that CS pups either produce more calls on PND-9 (Chiesa et al, 2020(Chiesa et al, , 2019Morais et al, 2020) or produce an equivalent number of calls (Castillo-Ruiz et al, 2018;Morais et al, 2021) or USVs with decreased amplitudes (Castillo-Ruiz et al, 2018) compared to VD counterparts, however, these studies were all in mice at a later stage of development than the current work. Our prior study of VD vole pups on PNDs 1 and 4 found that exposure to prenatal OXT led to increased USV production (Kenkel et al, 2019b).…”
Section: Discussioncontrasting
confidence: 76%
“…However, two other studies failed to find any association between birth mode and infant behaviour or CORT response to heel sticks during this time period 192,193 . In mice, CS results in pups emitting quieter isolation‐induced distress vocalisations 194 ; however, other studies have found CS results in greater vocalisation when tested later in development 195,196 . Further beyond birth, CS‐delivered human newborns show HPA‐axis hypo‐reactivity in the first few months postnatally 45,197 .…”
Section: Known Associations Of Caesarean Delivery With Developmental mentioning
confidence: 95%
“…192,193 In mice, CS results in pups emitting quieter isolation-induced distress vocalisations 194 ; however, other studies have found CS results in greater vocalisation when tested later in development. 195,196 Further beyond birth, CS-delivered human newborns show HPA-axis hypo-reactivity in the first few months postnatally. 45,197 We do not yet know the effects of birth mode on the HPA-axis, nor stress reactivity in childhood or further into development.…”
Section: Hpa-axis and Stress Reactivitymentioning
confidence: 99%
“…To our knowledge, no specific studies on the long term effects of C‐section on hippocampal‐dependent behaviour or hippocampal‐dependent synaptic plasticity have been performed so far. The only changes reported to date refer to early transient underdevelopment of dendritic arbour, associated to very mild variation of ultrasound vocalisation at postnatal day 9 (Chiesa et al., 2019, 2020). The present findings suggest that the long term consequences of mode of delivery require further studies as they might have also potential implications for investigating the etiopathogenesis of other CNS disorders.…”
Section: Discussionmentioning
confidence: 99%